Local communities's perceptions on rhino-tourism in Tabin Wildlife Reserve,Lahad Datu, Sabah - Zulhazman Hamzah; Fiffty Hanisdah Saikin; Maryati Mohamed (2011)
The host community is a fundamental component of any tourism system. Wildlife tourism and in this paper, rhino-tourism activities have many impacts on a host community : therefore, any increase in rhino-tourism as a recreational pursuit will inevitably be accompanied by a growth in numbers of local people affected by tourism. For the purpose of this paper, hosts are defined as those who live in the vicinity of the tourist attraction and are either directly or indirectly involved with, and/or affected by, the rhino-tourism activities. The host community is an important element to consider in the concept of sustainability. The sustainability of rhino-tourism is dependent, in part, on its support from the areas's residents. host satisfaction is related to both the involvement of local community members in rhino-tourism activities, and the benefits and disadvantages of rhino-tourism to host communities. Social and cultural issues need to be considered because of the importance of host acceptance to the overall sustainability of a rhino-tourism attraction. Determining how to make a rhino-tourism attraction sustainable from the perspective of the host community requires an understanding of the interplay of elements affecting both the perception of, and support for, that tourism. This paper will be discussed on the impacts and attitudes of local communities on regards to rhino-tourism in Tabin Wildlife Reserve, Lahad Datu, Sabah and based on the interviews, questionnaires and observations made, local communities living in the vicinity of Tabin Wildlife Reserve are very enthusiasm in rhino-tourism